An electro-osmotic microfluidic system to characterize cancer cell migration under confinement. Issue 155 (5th June 2019) - Hui, T. H.; Cho, W. C.; Fong, H. W.; Yu, M.; Kwan, K. W.; Ngan, K. C.; Wong, K. H.; Tan, Y.; Yao, S.; Jiang, H.; Gu, Z.; Lin, Y.
Abstract : We have developed a novel electro-osmotic microfluidic system to apply precisely controlled osmolarity gradients to cancer cells in micro-channels. We observed that albeit adhesion is not required for cells to migrate in such a confined microenvironment, the migrating velocity of cells is strongly influenced by the interactions between the cells and the channel wall, with a stronger adhesion leading to diminished cell motility. Furthermore, through examining more than 20 different types of cancer cells, we found a linear positive correlation between the protein concentration of the aquaporin-4 (AQP4) and the cell migrating speed. Knockdown of AQP4 in invasive re-populated cancer stem cells reduced their migration capability down to the level that is comparable to their parental cancer cells. Interestingly, these observations can all be quantitatively explained by the osmotic engine model where the cell movement is assumed to be driven by cross-membrane ion/water transport, while adhesion acts as a frictional resistance against the cell motility. By providing versatile and controllable features in regulating and characterizing the migration capability of cells, our system may serve as a useful tool in quantifying how cell motility is influenced by different physical and biochemical factors, as well as elucidating the mechanisms behind, in the future.